Lipase immobilised on silica monoliths as continuous-flow microreactors for triglyceride transesterification - Mohammed Alotaibi; Jinesh Manayil; Gillian Greenway; Stephen Haswell; Stephen Kelly; Adam Lee; Karen Wilson; Georgios Kyriakou (2018)
Lipase immobilised on silica monoliths has been prepared and applied as biocatalytic continuous-flow microreactors for the transesterification of tributyrin as a model bio-oil component. Candida antarctica lipase was trapped within the pores of silica monoliths, and its successful immobilisation was demonstrated by the hydrolysis of 4-nitrophenyl butyrate to 4-nitrophenol. Lipase immobilised on silica monoliths was active for the transesterification of tributyrin at ambient temperature, with reactivity as a function of the methanol[thin space (1/6-em)]:[thin space (1/6-em)]tributyrin ratio, flow rate, temperature, and textural properties. Monoliths with a high surface area and large meso- and macropore channels enhanced the transesterification activity through improved molecule diffusion. The optimum immobilised lipase microreactor exhibited almost quantitative ester production for >100 h at 30 °C without deactivation.